E-module with the Borg and Gall Model with a Contextual Approach to Thematic Learning - Putri, Septya Novena; Anak Agung Gede Agung; I Kadek Suartama (Universitas Pendidikan Ganesha, 2023)
The absence of digital teaching materials in the thematic learning process impacts student learning processes. Students tend to get bored quickly during learning, and teachers only use conventional teaching methods. This study aims to create a teaching material, namely E-module, based on a contextual approach to fifth-grade elementary school thematic learning. The subjects of this study consisted of 1 subject matter expert. One learning design expert, one learning media expert, results of individual trials of 3 students, and small groups of 9 people. This research is development research using the Borg and Gall development model. The method used for data collection is the method of questionnaires and tests—data analysis techniques using quantitative descriptive analysis and inferential statistical analysis. The results of the data analysis showed that the subject matter expert test obtained a score of 98%. Instructional design experts get a score of 98%. Learning media experts obtained a score of 89.33%. The individual test got a score of 95.33, and the small group test got a score of 96%. Based on these results, e-modules with a contextual approach to thematic learning are appropriate for learning activities. It is because e-module media can motivate students to participate in learning activities.